2007
DOI: 10.1124/jpet.106.118752
|View full text |Cite
|
Sign up to set email alerts
|

Subunit-Dependent Modulation of the 5-Hydroxytryptamine Type 3 Receptor Open-Close Equilibrium by n-Alcohols

Abstract: 5-Hydroxytryptamine (5-HT, serotonin) type 3 (5-HT 3 ) receptors belong to the alcohol-sensitive superfamily of Cys-loop ligandgated ion channels, and they are thought to play an important role in alcoholism. Alcohols with small molecular volumes increase the amplitude of currents evoked by low 5-HT concentrations and shift the 5-HT concentration-response curve for 5-HT 3 receptor activation leftward, indicative of increased receptor sensitivity to agonist. This action is significantly smaller when currents ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Therefore, we tested whether aliphatic n-alcohols also block 5-HT-induced currents. For some of these n-alcohols, a blocking action on dopamine but not on 5-HT-evoked currents has already been described [19]. Among the aliphatic n-alcohols, 1-octanol was the most effective at reducing currents by 94 ± 2 %, followed by longer chained 1-decanol (77 ± 3 %).…”
Section: Identification Of Negative Modulators Of the 5-ht 3a Receptormentioning
confidence: 91%
“…Therefore, we tested whether aliphatic n-alcohols also block 5-HT-induced currents. For some of these n-alcohols, a blocking action on dopamine but not on 5-HT-evoked currents has already been described [19]. Among the aliphatic n-alcohols, 1-octanol was the most effective at reducing currents by 94 ± 2 %, followed by longer chained 1-decanol (77 ± 3 %).…”
Section: Identification Of Negative Modulators Of the 5-ht 3a Receptormentioning
confidence: 91%
“…n -Alcohols enhance functions of GlyRs (Mascia et al, 1996a; Perkins et al, 2010) and most GABA A Rs (Mihic et al, 1997; Nakahiro et al, 1996), but suppress others such as α7nAChR and ρ1GABA A R (Cardoso et al, 1999; Covernton and Connolly, 1997; Mihic and Harris, 1996; Oz et al, 2005; Yu et al, 1996). Functional enhancement or suppression may depend on the molecular volume of alcohols and the receptor binding sites (Bradley et al, 1984; Cardoso et al, 1999; Nagata et al, 1996; Rusch et al, 2007; Stevens et al, 2005a; Stevens et al, 2005b; Wick et al, 1998). The phenomenon of alcohol cutoff (Pringle et al, 1981) has been observed for loss of righting reflex in tadpoles (Alifimoff et al, 1989) and also been observed in functional modulation of pLGICs (Dildy-Mayfield et al, 1996; Mascia et al, 1996a; Wick et al, 1998; Zuo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The 5-HT 3 B subunit imparts distinctive biophysical properties upon hetero-oligomeric 5-HT 3 AB versus homo-oligomeric 5-HT 3 A recombinant receptors 8,10,11,19,23,37,40, influences the potency of channel blockers, but generally has only a modest effect upon the apparent affinity of agonists, or the affinity of antagonists (5, but see 7,9,10) which may be explained by the orthosteric binding site residing at an interface formed between 5-HT 3 A subunits 25,47. However, 5-HT 3 A and 5-HT 3 AB receptors differ in their allosteric regulation by some general anaesthetic agents, small alcohols and indoles 17,38,39. The potential diversity of 5-HT 3 receptors is increased by alternative splicing of the genes HTR3A and E 6,14,31,33,34.…”
Section: -Ht3 Receptorsmentioning
confidence: 99%